Crash - Hagberg, David; Light, Lawrence (Forge, 2020)
"With debt-burdened governments and businesses worldwide about to go bust, a cabal of Wall Street big shots plot to destroy the globe's stock exchanges. To provide that one thing that goes wrong. In 24 hours, a powerful computer worm will smash the exchanges and spark an international panic, pushing a debt-laden world into the abyss. The Wall Street gang's investment bank will be the last one standing, able to make a killing amid the ruins. But one person, who works for their bank as a computer expert, spots the worm embedded deep in its network. Cassy Levin invents a program to destroy the cyber-intruder. Angered by Cassy's discovery, her bosses order her kidnapping. Her boyfriend, a former Navy SEAL, is alarmed at Cassy's disappearance and unravels the plot. Ben Whalen only has until the next morning to save the woman he loves and prevent the economic apocalypse."--